Noise as a Constructive Element in Music: Theoretical and Music-Analytical Perspectives - Delaere, Mark 1958- (Oxon Routledge, 2022)
Music and noise seem to be mutually exclusive. Music is generally considered as an ordered arrangement of sounds pleasing to the ear and noise as its opposite: chaotic, ugly, aggressive, sometimes even deafening. When presented in a musical context, noise can thus act as a tool to express resistance to predominant cultural values, to society or to socioeconomic structures (including those of the music industry). The oppositional stance confirms current notions of noise as something which is destructive, a belief not only cherished by hard-core rock bands but also shared by engineers and companies developing devices to suppress or reduce noise in our daily environment.In contrast to the common opinions on noise just described, this volume seeks to explore the constructive potential of noise in contemporary musical practices. Rather than viewing noise as a ‘defect’, this volume aims at studying its aesthetic and cultural potential.Within the noise music study field, most recent publications focus on subgenres such as psychedelic post-rock, industrial, hard-core punk, trash or rave, as they developed from rock and popular music. This book includes work on avant-garde music developed in the domain of classical music as well. In addition to already well-established (social) historical and aesthetical perspectives on noise and noise music, this volume offers contributions by music analysts.
PART II: Music-Analytical Case Studies: 6. Analysing Non-Score Based Music / Simon Emmerson -- 7. Noise in Spectral Music / Ingrid Pustijanac -- 8. Is There Noise in Helmut Lachenmann’s Music? Temporal Form and Moments of Presence in the String Quartet Gran Torso / Christian Utz -- 9. The Mic as a Scalpel – Skinning the Voice in Henri Chopin’s Sound Poetry / Jannis van de Sande -- 10. Noise as Ground in Improvised Music: The Case of Chris Corsano / Diederik Mark de Ceuster -- 11. Stretching Musicality to the Extreme: Vertical Composition in Merzbow’s Noise Music / Marina Sudo
Keywords: Noise; Music theory; Musical analysis